The potential anti-cancer effects of quercetin on blood, prostate and lung cancers: An update - Lotfi, Noushin; Yousefi, Zahra; Golabi, Marjan; Khalilian, Parvin; Ghezelbash, Behrooz; Montazeri, Mina; Shams, Mohammad Hossein; Baghbadorani, Parnian Zolfaghari; Eskandari, Nahid (Frontiers in Immunology, 2023)
Cancer is caused by abnormal proliferation of cells and aberrant recognition of the immune system. According to recent studies, natural products are most likely to be effective at preventing cancer without causing any noticeable complications. Among the bioactive flavonoids found in fruits and vegetables, quercetin is known for its anti-inflammatory, antioxidant, and anticancer properties. This review aims to highlight the potential therapeutic effects of quercetin on some different types of cancers including blood, lung and prostate cancers.